Sinaithyris, a New Name for the Middle Jurassic Terebratulid Brachiopod Cooperithyris Feldman, Radulović, Hegab, and Radulović, 2012 Preoccupied by Cooperithyris Tchorszevsky, 1988. (September 2014) - Feldman, Howard R.; Radulović, Vladan J.; Hegab, Adel A. A.; Radulović, Barbara V.
Abstract : Feldman, Radulović, Hegab, and Radulović (2012) established the genus Cooperithyris for an upper Bathonian terebratulid brachiopod from Gebel Engabashi, northern Sinai, based on the type species C. circularis Feldman, Radulović, Hegab, and Radulović, 2012. Recently, Professor Fernando Alvarez, (Departamento de Geologia, Universidad de Oviedo, Oviedo, Spain) informed us of the existence of the homonym Cooperithyris Tchorszevsky, 1988, from the Pliensbachian–Toarcian of the Transcaucasus. In accordance with the International Code of Zoological Nomenclature (ICZN 1999, articles 53 and 60), we herein propose the replacement name, Sinaithyris, for the junior homonym. The new name is in reference to the Sinai Peninsula on which Gebel Engabashi is located and from which the specimens were collected.